2020
DOI: 10.3389/fonc.2020.01510
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SREBP-2-Regulated Mevalonate Metabolism for Cancer Therapy

Abstract: Recently, targeting metabolic reprogramming has emerged as a potential therapeutic approach for fighting cancer. Sterol regulatory element binding protein-2 (SREBP-2), a basic helix-loop-helix leucine zipper transcription factor, mainly regulates genes involved in cholesterol biosynthesis and homeostasis. SREBP-2 binds to the sterol regulatory elements (SREs) in the promoters of its target genes and activates the transcription of mevalonate pathway genes, such as HMG-CoA reductase (HMGCR), mevalonate kinase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 232 publications
1
76
0
1
Order By: Relevance
“…Consistent with this, ESCRT-I depletion led to elevated expression of genes encoding enzymes of cholesterol biosynthesis (Fig. 4A), suggestive of impaired delivery of cholesterol from lysosomes to the ER (Luo et al, 2020;Xue et al, 2020). In accordance with this, we observed that ESCRT-I depletion in RKO cells led to the accumulation of cholesterol (stained by filipin) in enlarged LAMP1-positive structures (Fig.…”
Section: Depletion Of Escrt-i Inhibits Lysosomal Cholesterol Efflux That Does Not Contribute To Activation Of Tfeb/tfe3 Signalingsupporting
confidence: 84%
“…Consistent with this, ESCRT-I depletion led to elevated expression of genes encoding enzymes of cholesterol biosynthesis (Fig. 4A), suggestive of impaired delivery of cholesterol from lysosomes to the ER (Luo et al, 2020;Xue et al, 2020). In accordance with this, we observed that ESCRT-I depletion in RKO cells led to the accumulation of cholesterol (stained by filipin) in enlarged LAMP1-positive structures (Fig.…”
Section: Depletion Of Escrt-i Inhibits Lysosomal Cholesterol Efflux That Does Not Contribute To Activation Of Tfeb/tfe3 Signalingsupporting
confidence: 84%
“…Consistently, advanced breast cancers upregulate CYP27A1 while decreasing the expression of CYP7B1, thereby promoting 27HC accumulation (31,270). Higher levels of intracellular cholesterol in cancer cells are determined by aberrant HMGCR activity, due to disrupted sterol-controlled feedback regulation or SREBP-mediated overexpression (271)(272)(273). In hypoxic tumor microenvironments, SREBPs and their downstream genes are strongly upregulated and support cell survival and tumor growth (274).…”
Section: Oncogenic Signaling and Cholesterol Homeostasismentioning
confidence: 98%
“…Because of their rapid proliferation, cancer cells require high levels of cholesterol, and increased cholesterol biosynthesis is a hallmark of many cancers ( Figure 2 ). SREBP2 and its target genes are markedly upregulated in prostate cancer, breast cancer, and HCC [ 61 ]. Cholesterol biosynthesis also plays an important role in the maintenance of cancer stem cells by activating sonic hedgehog and Notch pathway [ 62 ].…”
Section: Cell-intrinsic Effects Of Lipid Metabolic Reprogramming Imentioning
confidence: 99%